Návrh a zhotovení zařízení pro osazování pájecích kuliček - Bobek, Josef (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2013)
Bakalářská práce se zabývá návrhem a konstrukcí zařízení pro osazování pájecích kuliček. První část práce obsahuje seznámení s typy, výrobou a osazování pájecích kuliček v praxi. Následující část pak zahrnuje samotnou práci na konstrukci zařízení, postupy, úvahy a dokončení prací na zařízení. Poslední část informuje o testování pájení osazených kuliček na stanici FRITSCH a porovnává případné chyby.

This work deals with issues of design and construction of facilities for mounting solder balls. The first part includes a familiarization with the types, manufacture and assembly of solder balls in practice. The following section includes the actual construction work on the equipment, procedures, considerations and finish work on the plant. The last part provides information about solder balls testing, which are mounted on the FRITSCH station, and compares potential errors.
Design and realisation of solder-ball mounting device
Keywords: Pájecí kuličky; inovace; pouzdra BGA; postupy pájení; FRITSCH; Solder balls; innovation; BGA packages; solder processes; FRITSCH